Quercitrin, the primary active ingredient of Albizia julibrissin Durazz. flowers, alleviates methamphetamine-induced hepatotoxicity through a mitochondria-mediated apoptosis pathway - Wu, Dan; Xie, Bo; Li, Jing; Xiao, Zhangang; Shen, Jing; Wu, Xu; Li, Mingxing; Sun, Qin; Shen, Hongping; Li, Xiaobing; Dai, Yong; Zhao, Yueshui (Frontiers in Pharmacology, 2025)
Background and purposeMethamphetamine (METH), a synthetic psychostimulant and highly addictive drug, could cause depression and acute liver injury. There have been few studies on the mechanism by which METH induces liver damage and on how to alleviate METH-induced hepatic toxicities. Albizzia julibrissin Durazz. flowers (AF) is a traditional Chinese medicine known for its ability to releve depression and soothe the liver. The extracts of AF have shown hepatoprotective effects with their anti-oxidative activities. The potential of AF extracts to alleviate METH-induced hepatic toxicity remains unclear. This study aims to investigate the effects of AF extracts and their priamry active ingredient on METH-induced hepatotoxicity and explore the potential underlying mechanisms.MethodsFirstly, we used the MTT assay to screen the active components of AF. Then, UPLC-MS/MS was employed to analyze the effective components and identify their activities. In addition, in vitro and in vivo experiments were conducted to explore the effects of the active components on METH-induced hepatic toxicity. Moreover, flow cytometry was employed to detect the effects of the active components of AF on METH-induced hepatocyte cycle arrest and apoptosis; biochemical kits were used to detect oxidative damage; transmission electron microscopy, mitochondrial membrane potential probes, and Western blotting were used to analyze mitochondrial damage. C57/BL6J mice were used to establish a METH-mediated acute liver injury model. After 21 days of intervention with the effective components of AF, serum from mice was collected to detect the level of liver injury markers, and tissues were collected for H&E staining, oxidation index analysis, and mitochondrial-related protein expression analysis.ResultsWe found that the ethyl acetate fraction of AF extracts significantly alleviated the decrase in hepatocyte activity induced by METH in vitro. Further UPLC-MS/MS analyses showed that quercitrin (QR) is the major active ingredient of AF extracts. QR alleviates METH-induced hepatocyte apoptosis, cell cycle arrest, oxidative stress, and mitochondrial damage. QR alleviates METH-induced oxidative liver damage in mice and exerts therapeutic effects by regulating the BAX/CASP3 pathway.ConclusionAF and its main component QR can effectively alleviate METH-induced liver injury, and its mechanism is related to the mitochondria-mediated apoptotic pathway.